Procyanidin B2 alleviates liver injury caused by cold stimulation through Sonic hedgehog signalling and autophagy. Issue 16 (21st June 2021) - Ma, Li; Li, Chengxu; Lian, Shuai; Xu, Bin; Lv, Hongming; Liu, Yanzhi; Lu, Jingjing; Ji, Hong; Li, Shize; Guo, Jingru; Yang, Huanmin
Abstract: Procyanidin B2 (PB2), a naturally occurring flavonoid abundant in a wide range of fruits, has been shown to exert antioxidant, anti‐inflammatory and anticancer properties. However, the role of PB2 in the prevention of cold stimulation (CS)‐induced liver injury. The present study was undertaken to determine the effects of PB2 on liver injury induced by cold stimulation and its potential molecular mechanisms. The present study results showed that treatment with PB2 significantly reduced CS‐induced liver injury by alleviating histopathological changes and serum levels of alanine transaminase and aspartate transaminase. Moreover, treatment with PB2 inhibited secretion of inflammatory cytokines and oxidative stress in cold‐stimulated mice. PB2 reduced cold stimulation‐induced inflammation by inhibiting TLR4/NF‐κB and Txnip/NLRP3 signalling. Treatment with PB2 reduced oxidative stress by activating Nrf‐2/Keap1, AMPK/GSK3β signalling pathways and autophagy. Furthermore, simultaneous application of Shh pathway inhibitor cyclopamine proved that PB2 targets the Hh pathway. More importantly, co‐treatment with PB2 and cyclopamine showed better efficacy than monotherapy. In conclusion, our findings provide new evidence that PB2 has protective potential against CS‐induced liver injury, which might be closely linked to the inhibition of Shh signalling pathway.